2007
DOI: 10.15517/rbt.v56i3.5699
|View full text |Cite
|
Sign up to set email alerts
|

Zoo-heleoplankton structure in three artificial ponds of North-eastern Argentina

Abstract: Abstract:The aim of the present study was to compare the abundance and species richness of zoo-heleoplankton bigger than 53 µm in an annual cycle under similar climate conditions in three artificial ponds, in order to observe the changes during an annual cycle. Samples were taken monthly from June 1993 to July 1994 in Corrientes, Argentina. The first pond (A) was covered an 80% by Eichhornia crassipes (Mart.), the second one (B) with bloom of Microcystis aeruginosa (Kurtzing) and the last one (C) with organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…The characteristics of both lakes tended towards a more similar state in the dry periods during the study, with higher abundance of filter feeders. Frutos and Carnevali (2008) observed a higher abundance of zooplankton in an artificial lake dominated by cyanobacteria than in a similar-sized lake dominated by macrophytes, and Frutos et al (2009) observed peaks of zooplankton in eutrophication events in two lakes in the Corrientes region, Argentina. Higher densities of zooplankton have also been observed in floodplain lakes of the Pantanal during the low-water phase (Fantin-Cruz et al 2011).…”
Section: Effects Of Depletion On the Cladoceran Communitymentioning
confidence: 98%
“…The characteristics of both lakes tended towards a more similar state in the dry periods during the study, with higher abundance of filter feeders. Frutos and Carnevali (2008) observed a higher abundance of zooplankton in an artificial lake dominated by cyanobacteria than in a similar-sized lake dominated by macrophytes, and Frutos et al (2009) observed peaks of zooplankton in eutrophication events in two lakes in the Corrientes region, Argentina. Higher densities of zooplankton have also been observed in floodplain lakes of the Pantanal during the low-water phase (Fantin-Cruz et al 2011).…”
Section: Effects Of Depletion On the Cladoceran Communitymentioning
confidence: 98%
“…Not much is known about the effect that aquatic vegetation has on habitat differentiation and on plankton occurrence in ponds. The available data on heleoplankton usually comes from temporal studies, in annual or long-term cycles [1920], mainly concerning the open water area. Macrophytes also influence abiotic parameters [21] and have an impact on relationships between organisms in the aquatic food web [22].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, I. paranaensis paranaensis has been considered the only species occurring in South America, with reports from Argentina (Paggi, 1989;Frutos and Carnevali, 2008) and Brazil (Kotov and Elmoor-Loureiro, 2008 Ilyocryptus paranaensis inarmatus, representing the first record for South America. A single specimen of I. paranaensis inarmatus was found in a sample taken with a plankton net (100 mm mesh) among submerged macrophytes and fixed with 4% formalin, during the dry season (August/2009) in Mestre D'Armas stream (15° 39' 40,4" S and 47° 40' 38,1" W), in the Federal District, Brazil (0.37 m deep, pH 6.2, electric conductivity 134.9 mS/cm, dissolved oxygen 2.27 mg/L, current velocity 0.5 m/s).…”
mentioning
confidence: 99%